The stratigraphic significance of trace fossils from the Lower Paleozoic Baskahegan Lake Formation near Woodstock, west-central New Brunswick - Pickerill, R.; Fyffe, L. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1999)
The first indication of organic activity in Lower Paleozoic siliciclastic turbidites of the Miramichi Terrane has been found in a small quarry at Grafton Hill, near Woodstock, west-central New Brunswick. These previously unnamed turbidites are assigned to the Baskahegan Lake Formation defined in adjacent Maine. The Grafton Hill site has yielded the ichnotaxa Circulichnis montanus, Gordia? marina, Helminthopsis hieroglyphica, Planolites annularius and Planolites montanus. The presence of Circulichnus montanus supports previous circumstantial evidence that a considerable part of the Baskahegan Lake Formation is Early Ordovician in age and substantiates correlation with other quartz-rich peri-Gondwanan sequences elsewhere in the Appalachian-Caledonide Orogen.